Tranexamic acid administration and pulmonary embolism in combat casualties with orthopaedic injuries. Issue 4 (19th December 2021) - Hoyt, Benjamin W.; Baird, Michael D.; Schobel, Seth; Robertson, Henry; Sanka, Ravi; Potter, Benjamin K.; Bradley, Matthew; Oh, John; Elster, Eric A.
Abstract : Objectives: In combat casualty care, tranexamic acid (TXA) is administered as part of initial resuscitation effort; however, conflicting data exist as to whether TXA contributes to increased risk of venous thromboembolism (VTE). The purpose of this study is to determine what factors increase risk of pulmonary embolism after combat-related orthopaedic trauma and whether administration of TXA is an independent risk factor for major thromboembolic events. Setting: United States Military Trauma Centers. Patients: Combat casualties with orthopaedic injuries treated at any US military trauma center for traumatic injuries sustained from January 2011 through December 2015. In total, 493 patients were identified. Intervention: None. Main Outcome Measures: Occurrence of major thromboembolic events, defined as segmental or greater pulmonary embolism or thromboembolism-associated pulseless electrical activity. Results: Regression analysis revealed TXA administration, traumatic amputation, acute kidney failure, and hypertension to be associated with the development of a major thromboembolic event for all models. Injury characteristics independently associated with risk of major VTE were Injury Severity Score 23 or greater, traumatic amputation, and vertebral fracture. The best performing model utilized had an area under curve  = 0.84, a sensitivity=0.72, and a specificity=0.84. Conclusions: TXA is an independent risk factor for major VTE after combat-related Orthopaedic injury. Injury factors including severe trauma, major extremity amputation, and vertebral fracture should prompt suspicion for increased risk of major thromboembolic events and increased threshold for TXA use if no major hemorrhage is present. Level of evidence: III, Prognostic Study